The World of Rules: A Somewhat Different Measurement of the World - Gunnar Folke Schuppert (Max Planck Institute for European Legal History, 2017)
This book takes a stand against the narrowing focus of (German) jurisprudence on state law, rooted in the history of the territorially organised nation state. In the shadow of this tradition, state(-hood) law was only conceived of as state law. However, a gradual decoupling of state and law is observable – not least because of globalisation – which inevitably entails a pluralisation of legal regulations. Jurisprudence has to react to this, if it wants to remain relevant.
urn:nbn:de:101:1-201801223853; Additional information: Translated from the German original by Rhodes Barrett.
Keywords: 300; law; statuary regulation; governance; social norm; jurisdiction; adherence to norms; justice